2004
DOI: 10.1017/s0033291703001582
|View full text |Cite
|
Sign up to set email alerts
|

Defining nicotine dependence for genetic research: evidence from Australian twins

Abstract: Background. Whether current criteria used to define nicotine dependence are informative for genetic research is an important empirical question. The authors used items of the DSM-IV and of the Heaviness of Smoking Index to characterize the nicotine dependence phenotype and to identify salient symptoms in a genetically informative community sample of Australian young adult female and male twins.Method. Phenotypic and genetic factor analyses were performed on nine dependence symptoms (the seven DSM-IV substance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
153
0
6

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 176 publications
(170 citation statements)
references
References 76 publications
(79 reference statements)
11
153
0
6
Order By: Relevance
“…19,21,27 A genetic influence on nicotine withdrawal symptoms and smoking cessation has also been identified with heritability estimated at 26-48 and 50-58%, respectively. [28][29][30] Taken together, these studies suggest a substantial genetic contribution to most aspects of smoking. It should be noted that genetic risk factors for different aspects of smoking (such as initiation and persistence) only partially overlap, suggesting some genes will be specific to one smoking phenotype whereas others may influence multiple aspects of smoking.…”
Section: Introductionmentioning
confidence: 69%
“…19,21,27 A genetic influence on nicotine withdrawal symptoms and smoking cessation has also been identified with heritability estimated at 26-48 and 50-58%, respectively. [28][29][30] Taken together, these studies suggest a substantial genetic contribution to most aspects of smoking. It should be noted that genetic risk factors for different aspects of smoking (such as initiation and persistence) only partially overlap, suggesting some genes will be specific to one smoking phenotype whereas others may influence multiple aspects of smoking.…”
Section: Introductionmentioning
confidence: 69%
“…CPD was selected as the single phenotype for analysis, because it is a highly heritable, 3 widely used phenotype in genetic studies of smoking. 7,8,10 To understand the relationship between CPD and DSM-IV ND, we analyzed an epidemiologic dataset, the National Epidemiologic Survey of Alcohol and Related Conditions (NESARC 11 ).…”
Section: Methodsmentioning
confidence: 99%
“…The twin studies suggest that a majority of risk for nicotine dependence (ND) may be attributable to genetic factors. More recent twin smoking research [3][4][5] suggests that the heritability of ND is even higher.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Twin and family studies have suggested a high heritability (56-75%) for ND; [3][4][5][6][7] clearly, social, psychological and other environmental factors as well as comorbidities, such as alcohol use and depression, contribute as well. 8,9 Several genome-wide scans have been performed suggesting loci linked to smoking behavior and ND.…”
Section: Introductionmentioning
confidence: 99%